PENGARUH GAYA KEPEMIMPINAN, KOMPETENSI SERTA BUDAYA KERJA DIDALAM ORGANISASI TERHADAP KINERJA KERJA PEGAWAI KANTOR PUSAT BPJS KESEHATAN - Sugiarto, Irsan; Djati, S. Pantja (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
The purpose of the study examines the influence of leadership style, and competence on work performance, by using work culture as a mediation between leadership style and competence on work performance. This study took a random sample with 84 samples taken from 510 populations with employee levels taken from executors to managers, while the research method used path analysis. The results found in this study are where leadership styles and competencies influence work culture, which later between leadership style, competence, and work culture influence the performance of Employees on Headquarters BPJS Kesehatan.